Vertex‐Transitive Graphs of Prime‐Squared Order Are Hamilton‐Decomposable. Issue 1 (15th October 2013) - Alspach, Brian; Bryant, Darryn; Kreher, Donald L.
Abstract We prove that all connected vertex‐transitive graphs of order p2, p a prime, can be decomposed into Hamilton cycles.